Some Thoughts on Arab-Islamic Art - Čelić, Džemal (Prilozi za orijentalnu filologiju, 2017)
The author presents his views on some issues of the Islamic art, put forward previously at the Conference „On Ararb-Islamic Culture“, which took place in Sarajevo on May 18 and 19, 1973. The Arab-Islamic art appears as a variety and continuation of the late Roman, Hellenic and Byzantine cultural and artistic heritage .with the Persian-Sassanid component. That art was created on these foundations, and in the continuity of creativity of the Ancient World it was a bridge between Graeco-Roman and Byzantine art, and the Renaissance and the later European tendencies in style. The philosophy phenomenon of Islam is based on the Mesopotamian and Babylonian concept of the ruler, who is God's representative on earth, and who conveys the Divine Law to people, which was exceptionally conspicuous in the well-known of Hammurabi. Otherwise, the conception of the state in which the ruler is also the supreme priest, was important not only for Mesopotamia and Egypt, but for the Roman Empire and Byzantium as well. The appearance of Islam had the effect of the reform of Bysantinism; beginning with theological discussions of monotheism and trinity, through the controversy over Ceasar and Pope of the successors of Constantine, to iconoclastic disputes - all the key social and ideological points of conflict of the Byzantium – were definitely resolved in Islam. Islam included energetic monotheism, „God's shadow on earth“, instead of Ceasar and the Pope. It was against clergy and pictures in the service of religion. In the chapter on „The problem of figurative art in Islam“ it was pointed out, that not only Islam, but Christianity as well, opposed the figure in its early stage, and the picture was looked upon as a concession to uneducated masses of people. As for Islam, there is plenty of reason to question the thesis about prohibition of figurative art. There is no definite ban either in the Koran, or in the Hadith, or rather, the whole problem seems to apply to the figure in the service of idolatry exclusively. The cleaning up of the Kaaba and the mocking down and breaking of the idols, had actually been the final settling of accounts with the enemy, rather than with figurative art. That is, the tradition has it, that at the moment of the cleaning up of the Kaaba, Muhammed protected, by his own authority, the image of the Virgin and Jesus Christ that had been there (it was destroyed in the battle in Mecca in 683). The attitude towards that image should not be understood as an act of tolerance towards the Christians, but as an attitude towards a work of art - in that case, the portrait of the concrete historical personalities. A large number of the later examples of fresco-decorations, reliefs with birds, animals and human figures, sculptures included into buildings, miniatures in the Islamic books, objects in wood, metal, ceramics or textile, indicate that figure co-existed with abstraction in the Islamic world. Besides, although it had been mostly connected with profane architecture, literature and the objects used in everyday life, it did not entirely avoid the religious subject-matter, or the sacral buildings, especially in the eastern part of the Islamic world. The reasons for suppression of figure in the Islamic art, do not, probably, lie in the ban. They are primarily the result of the Islamic concept of God, or rather, the God's properties. God in Islam is a totally abstract idea, defined mostly by negations, or the concepts that lie outside the sensory perception. There was nothing that could be artistically presented, without, thereby, giving the God the attributes which would mean blasphemy. Therefore, it was not the ban, but inability to give a ·realistic picture, that stopped the Islamic arti1st when he reached for the transcendental. The same happened in Judaism, with the famous frescoes of the synagogue in Dura Europos, while in Christianity. the idea of incarnation of God in man, had been crucial for introducing of the transcendental .into the sphere of form. - The abstract thought could best be mastered by means of letters. That is why calligraphy occupies such an exceptional place in the Islamic art. The artistic value of letters strengthens the association with God. The need for obligatory legitimacy of the authorities, which also demanded their place in the temples, urged the authorities to accept the same means of expression, which was very convenient in emphasizing of the connection between God and the ruler. In the chapter under the title „The roots of the concept of space of the first great mosques“ the importance of Amr-ibni-el-Asa Mosque in Fustat (in Cairo), the first great mosque in the Islamic world after Muhammed's mosque in Medina, was pointed out, as well as the importance of the mosque in Qufa which was not so well preserved. In the mosque of Fustat, the considerable influence of the Old-Egyptian temples on the conception of the first mosques can be discerned. The influence of the Persian, was in the present author's opinion unduly emphasized, while the Sassanid had been present in the conception of the Islamic temple only since the time of the Seljuks. His application was a convincing proof of the decline of early-Islamic, autocratic society, and its transformation into complex structures of feu dal society.